(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Blaptica dubia is a cockroach that used as feed for most reptiles and amphibians because of it nutritive value. Its alternative protein sources can replace the current high priced imported animal feed such as fishmeal, soybeans and meat. It has potential as an animal feed and minimize high livestock farming cost of the farmers. A study was conducted to determine the nutritional composition (moisture, ash, crude protein, chitin and fat) of B. dubia in different growth stages. Moisture and ash determine using AOAC protocol, protein using Kjeldahl method, chitin using chemical treatment and fat analysis using soxhlet extraction method. The proximate analysis of adults and nymph of B. dubia contained 59.06-62.70% moisture, 2.47-4.17% ash, 47.50-54.32% crude protein, 3.83-5.58 % chitin and 35.49-44.22% fat on dry weight. Thus, the tested feed pellets could be an alternative protein source as the animal feed especially in pet industry.